2011
DOI: 10.2965/jwet.2011.13
|View full text |Cite
|
Sign up to set email alerts
|

Removal of Selenium (VI) from Simulated Wet Flue Gas Desulfurization Wastewater Using Photocatalytic Reduction

Abstract: The removal of Se(VI) from a simulated wet flue gas desulfurization (FGD) wastewater was attempted by the use of a photocatalytic reduction system. Conventional method of removal, such as adsorption by ion-exchange resins, was not effective for Se(VI) removal from wastewater. The photocatalyst reduction system consisted of TiO 2 and HCOOH as a photocatalyst and an electron hole scavenger, respectively. When the photo-irradiation was performed for a Se(VI) solution under the system, an efficient removal of Se(V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…A synthetic flue gas desulfurization (FGD) wastewater was developed and used in fouling experiments based off of the wastewater created in the studies by Nakajima et al [26]. Fouling experiments using this wastewater were to be used as a determinant of the applicability of ceramic membrane treatment at elevated temperatures for FGD wastewater in coal-fired power plants.…”
Section: Feed Solutionsmentioning
confidence: 99%
“…A synthetic flue gas desulfurization (FGD) wastewater was developed and used in fouling experiments based off of the wastewater created in the studies by Nakajima et al [26]. Fouling experiments using this wastewater were to be used as a determinant of the applicability of ceramic membrane treatment at elevated temperatures for FGD wastewater in coal-fired power plants.…”
Section: Feed Solutionsmentioning
confidence: 99%
“…In this regard, an earlier work on TiO 2 photocatalytic reduction of selenium oxyanions was carried out by Kikuchi et al [23] Since then, these systems have been examined by several other groups. [24][25][26][27][28][29][30][31][32][33][34][35][36] Many of these studies have also investigated the role of hole (h + ) scavengers such as formic acid during TiO 2 -assisted photocatalytic reduction of selenite and selenate and report significant removal of selenium contamination from the aqueous phase. [24][25][26][27][28] Recently, Aman et al [36] also reported using a modified Ti-Zrbased photocatalyst and EDTA (as a hole scavenger) for selenite/selenate removal from the aqueous phase.…”
Section: Introductionmentioning
confidence: 99%
“…Existing work that tests emerging technologies for FGD wastewater treatment does not explicitly take into account intra- and interplant variability. Instead, much of the published literature that evaluates the efficacy of FGD wastewater treatment technologies tested process performance using grab samples collected from CFPPs , or synthetic wastewaters based on average concentrations reported in the literature. , Both approaches ignore the intra- and interplant variability found in sampling campaigns and our results. Instead, BAT performance should be demonstrated on the full range of characteristic feedwater concentrations.…”
Section: Discussionmentioning
confidence: 99%